With each tomorrow [large type] - Peterson, Tracie; Woodhouse, Kimberley, 1973- (Peterson, Tracie. Jewels of Kalispell, 2024)
"Even in the midst of adversity, love and faith can flourish. As the formation of Glacier National Park takes Eleanor Briggs and her conservationist father on a journey west to advocate for public lands, her heart carries the weight of a painful past. Since the death of her mother, she has spent her life traveling the country with her father and helping him with his work, but now he's considering settling down and writing a book--and she's not sure what that means for her future.Carter Brunswick faces trials of his own when the Great Northern Railway's departure threatens his family's livelihood and the entire town of Kalispell. In the visiting conservationist's daughter, Ellie, he finds a spirited woman who challenges his convictions in ways he never anticipated, and his own dreams for the future begin to change.When tensions over the railroad's departure boil over, Ellie and Carter are drawn together on a daring journey that tests the depths of their feelings and their faith in God"--